Bladder capacity as a benchmark for patient stratification in interstitial cystitis/bladder pain syndrome - Maxwell Sandberg; Dylan T. Wolff; Wyatt Whitman; Gopal Badlani; Catherine A. Matthews; Robert Evans; Stephen J. Walker (Continence, 2023)
Objectives:: In a previous study we reported that molecular profiling of bladder mucosal tissue from a modest number of IC/BPS patients resulted in a clear separation based on anesthetic bladder capacity (BC), with 400 cc representing the apparent breakpoint between low and non-low BC. The purpose of the current study was to revisit this earlier stratification finding, using a combination of molecular and clinical data, from a large and heterogeneous patient cohort. Materials and Methods:: To provide an updated assessment of IC/BPS patient stratification based on anesthetic BC, whole genome gene expression data from 48 mucosal biopsy samples (41 IC/BPS patients; 7 controls) were analyzed with unsupervised clustering and principal component analysis (PCA) to identify primary clusters of patients. This identified three primary individual clusters: (1) IC/BPS patients with a BC between 200–500 cc (n=19), (2) IC/BPS patients with a BC of 501–1500 cc (n=22), and (3) controls. Next, complete demographic, clinical, and questionnaire data prospectively collected from an additional 450 patients from our patient registry were used to conduct a combined analysis to verify this relationship. Characteristics of all 491 IC/BPS patients were compared between those having the current low BC cutoff (≤400 cc) and the proposed new cutoff (≤500 cc) by utilizing independent samples t-test (continuous variables) and chi square tests (categorical variables; p ≤ 0.05 was considered significant). Results:: A statistical comparison of the demographic and clinical characteristics of the entire 491 IC/BPS patient cohort showed that those with a bladder capacity ≤500 cc were older, were more likely to have Hunner lesions, and had higher symptom scores. This group also had a lower average number of non-urologic associated symptoms, pelvic pain syndromes, and neurologic, immune, or systemic pain syndromes. Conclusion:: By combining newly acquired molecular data with clinical and demographic characteristics in a large cohort of IC/BPS patients, we conclude that anesthetic BC ≤ 500 cc provides a clinically meaningful biomarker for the bladder centric IC/BPS phenotypic subgroup.